DESIGNED-IN SCAFFOLDING: SUPPORTING EFL YOUNG LEARNERS IN CREATING MULTIMODAL TEXTS - TIRA ROSTIA WARNDINI; IKA LESTARI DAMAYANTI; LULU LAELA AMALIA (LINGUISTICA, 2023)
The research explored the designed-in scaffolding features implemented by the teacher in the English as a foreign language (EFL) young learner classroom to support young learners in creating multimodal texts. The research used scaffolding theory proposed by Hammond and Gibbons (2005) which categorized scaffolding into two fragments: designed-in and interactional scaffolding. The research was conducted in one of the elementary schools in Bandung. It involved one teacher who taught 18 students in 4th grade. The data were gained from classroom observation and teacher’s lesson plans. The findings revealed that the features of designed-in scaffolding were employed by the teacher in planning and implementing the lesson in the classroom. This research also found that following the designed-in scaffolding features could lead the teacher to structure and provide activities, tasks, and multimodal exposures for the students to be familiar with the multimodal texts. Hence, this research resulted in the pedagogical implication to encourage the teacher to be aware of scaffolding. If the teacher could provide an appropriate scaffolding, the students could gain the assistances, supports, and multimodal exposure for young learners to learn and create multimodal texts.